Evaluation of neurophysiological properties among methadone treatment subjects: EEG and ERP study / Farid Esmaeili Motlagh - Farid Esmaeili , Motlagh (2018)
This thesis presents the investigation of brain electrophysiological attributes of heroin addicts from early stages of withdrawal until three months of methadone maintenance treatment (MMT) with and without electroacupuncture (EA). In this longitudinal study, 96 heroin-dependent subjects had been recruited to MMT program and divided randomly into two groups of MMT+EA and MMT. A comprehensive paradigm was designed to probe the event-related potential (ERP) components and a novel single-trial algorithm was developed to detect and extract the ERP components features. EEG power spectrum and electro-cognitive responses were the main assessments to be evaluated in each phase of the study. The first phase was a cross-sectional study between heroin dependents and healthy control subjects. Study subjects went through three months of treatment, and neurophysiological properties were assessed based on monthly interventions. This study has further confirmed that opioid addiction significantly influences certain brain regions and causes abnormal spectral activity, as well as the decline of brain evoked potentials amplitudes. Monitoring the immediate and short-term effects of treatment revealed the process of cognitive enhancement among the subjects. Furthermore, the results of different phases suggest electro-neurophysiological properties as an index indicate cognitive dysfunction and severity of brain activity dysregulations which can be used for evaluating the treatment effectiveness as well. The results also proved the reliability of single-trial ERP detection algorithm and suggested the employment of this paradigm in the field.